2021
DOI: 10.3390/ijms22041511
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Microbial Signatures and Gut-Brain Crosstalk in Pediatric Patients with Coeliac Disease and Type 1 Diabetes Mellitus

Abstract: Coeliac disease (CD) and Type 1 diabetes mellitus (T1DM) are immune-mediated diseases. Emerging evidence suggests that dysbiosis in the gut microbiome plays a role in the pathogenesis of both diseases and may also be associated with the development of neuropathy. The primary goal in this cross-sectional pilot study was to identify whether there are distinct gut microbiota alterations in children with CD (n = 19), T1DM (n = 18) and both CD and T1DM (n = 9) compared to healthy controls (n = 12). Our second goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 101 publications
1
8
0
Order By: Relevance
“…We found that several taxa were decreased in the age 1 CD progressor samples, such as Veillonella, Enterobacteriaceae, and Bacteriodes. This is consistent with other studies showing Veillonella decreased in CD progressors 72 , Enteriobacter decreased in infants at high risk for CD 71 and Bacteroides decreased in both CD progressors 72 and patients 69 . Consistent with our findings, other studies have shown that the abundance of B. dentium was increased in the CD patients 73 .…”
Section: Discussionsupporting
confidence: 93%
“…We found that several taxa were decreased in the age 1 CD progressor samples, such as Veillonella, Enterobacteriaceae, and Bacteriodes. This is consistent with other studies showing Veillonella decreased in CD progressors 72 , Enteriobacter decreased in infants at high risk for CD 71 and Bacteroides decreased in both CD progressors 72 and patients 69 . Consistent with our findings, other studies have shown that the abundance of B. dentium was increased in the CD patients 73 .…”
Section: Discussionsupporting
confidence: 93%
“…T1D is a systemic autoimmune disease that is linked to microbial dysbiosis. Preclinical and clinical T1D is mostly associated with GIT pathogenesis, such as celiac disease or increased intestinal leakage potentially due to microbial dysbiosis ( 41 – 43 ). Multiple studies report significant shifts in gut microbes including bacteria, viruses, and fungi before the onset of T1D as reviewed ( 44 ).…”
Section: Microbial Dysbiosis Drives Systemic Autoimmune Diseasesmentioning
confidence: 99%
“…[ 114 ] suggested that gut-related inflammation elicits neuroinflammation by endocrine signals and, therefore, promotes atrophy and hyperactivity in the anterior cingulate cortex, involved in mood disorders, anxiety, and threat-related behaviors [ 114 ]. The “leaky gut” condition in CD also encourages the overproduction and release of LPS and long-chain fatty acids, which both play a central role in neuronal plasticity [ 115 , 116 ] and neurodegeneration [ 117 , 118 , 119 ].…”
Section: Celiac Disease Gut Microbiota and Inflammationmentioning
confidence: 99%